Permutations of Remembrance and (Counter-) Monumentalization: John Mccrae’s in Flanders Fields - Branach-Kallas, Anna (Studia Anglica Posnaniensia, 2020)
The article engages with the cultural impact of John McCrae’s canonical poem “In Flanders Fields” (1915), and more specifically the permutations of cultural memory and heritage discourse in In Flanders Fields: 100 Years: Writing on War, Loss and Remembrance, edited by Amanda Betts and published in 2015. It shows how thirteen Canadians explore the revolutionary role of the poem in Canadian collective and individual memory, as well as its omissions and misrepresentations. The article juxtaposes the cultural history of the poem with Wilfred Owen’s “Dulce et Decorum Est” and its contemporary transformations, also showing how selected essays in the collection bridge the First World War with other armed conflicts. Applying Ann Rigney’s terminology, the article approaches the poem as a textual monument, demonstrating how “In Flanders Fields” has evolved from the role of a stabilizer in Canadian cultural memory, providing a cultural frame for later recollections, to that of a calibrator, becoming a benchmark for critical reflection on dominant memorial practices.